New fossil turtle remains from the Eocene of the Antarctic Peninsula - Bona, Paula; de la Fuente, Marcelo Saul; Reguero, Marcelo Alfredo (Antarctic Science)
The fossil record of reptiles from the Paleogene of Antarctica 13 is very scarce. Only postcranial fragments of Dermochelyidae 14 turtles have been recovered from several localities on Isla 15 Marambio (Seymour Island, fig. 1 in de la Fuente et al. 1995, 16 Albright et al. 2003). The fossils described by de la Fuente 17 et al. (1995) include a few isolated carapace ossicles and a 18 small fragment of carapace with four sutured ossicles, and 19 were tentatively assigned by these authors to the leatherback 20 turtle Psephophorus, a genus whose species are recorded 21 from the middle to upper Eocene–Pliocene of Europe, New 22 Zealand, and North America (see discussion about the 23 taxonomic status of Psephophorus in Wood et al. 1996). 24 Posteriorly, new and more complete material was reported by 25 Albright et al. (2003). These authors provisionally assigned 26 this specimen to ‘‘Psephophorus’’ terrypratchetti Ko¨hler, a 27 species from upper Lutetian of South Island, New Zealand. In 28 this contribution we describe two turtle carapace plates 29 recently recovered from the middle levels (Cucullaea I 30 Allomember) of the La Meseta Formation, Isla Marambio 31 (Marenssi 2006). This material represents the first record of a 32 turtle with a bony carapace from the Eocene of Antarctica, and 33 it increases the diversity of the group on this continent. Fil: Bona, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: de la Fuente, Marcelo Saul. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Museo Municipal de Historia Natural San Rafael - Unidad Asociada al CCT Mendoza; Argentina Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y ...